Online learning amidst crisis: perceptions of Gazan university students - Khasawneh, Razan; Alsharif, Bilal; Khasawneh, Ronza (Frontiers in Education, 2025)
In light of the challenges and crises the world is facing, the usage of technology has a significant impact on students’ perceptions and learning experiences. This study investigates the perceptions of Gazan university students toward online learning in the context of an ongoing crisis. Using a qualitative thematic analysis methodology, this study conducted semi-structured interviews with a random sample of fifteen graduate students (eight females and seven males) from Gaza University. It aimed to to shed light on Gazan students’ perceptions regarding online learning follwoing the events of October 7th to provide viable solutions that could help them receive appropriate education. The thematic analysis revealed several key findings. Students expressed both gratitude for the continuity of their education and significant frustration with logistical challenges, including inconsistent internet access and frequent power outages. The interviews also highlighted the psychological toll of the crisis, which often impeded their ability to concentrate and engage in online coursework. Students also have a positive perception regrding the convenient, on-demand access to lectures and course content that online learning provides. These findings underscore the dual nature of online learning in a conflict zone: it serves as both a critical lifeline and a source of new stressors. The findings are anticipated to have crucial practical implications for higher education institutions in Gaza, staff, policymakers, and the Ministry of Education aiming to design and implement strategic online education systems that are not only accessible but also resilient and supportive.